Effect of Tamsulosin on Treatment of Lower Ureteric Calculi - Rahman, Md Mostafiger; Johura, Fatema Tui; Ali, Mohammad Ibrahim; Hossain, Md Sazzad; Islam, Md Kamrul (Bangladesh Journal of Urology, 2020)
Introduction: Medical expulsive therapy (MET) is one of the treatment modality for ureteric calculi. Recent studies have reported excellent results with MET for lower ureteral calculi. The aim of study to evaluate the effect of tamsulosin on treatment of lower ureteric calculi. Materials and Methods: A prospective study was conducted at outpatient department of Urology, Prime Medical College Hospital, Rangpur, Bangladesh during February 2018 to February 2019. A total of 100 patients with lower ureteric calculi included in this study. Cases were selected by inclusion and exclusion criteria and randomly allocated in two groups. Tamsulosin group (50 patients) were given capsule tamsulosin 0.4 mg, at bed time while observation group (50 patients) were given standard therapy without tamsulosin. The patients were prescribed diclofenac (50 mg) on demand for pain relief and were followed-up by X ray and ultrasonography of kidney, ureter and urinary bladder region for 28 days. The stone expulsion rate, expulsion time, and analgesic requirements were also recorded. Data were analyzed and compared by statistical tests. Results: Tamsulosin group showed a statistically significant advantage in terms of the stone expulsion rate. A stone expulsion rate of 78% (39 out of 50 patients) in tamsulosin group and 54% (27 out of 50 patients) was observed for observation group (p=0.011). In tamsulosin group, mean expulsion time was 7.26 ±3.35 days whereas in observation group mean expulsion time of 8.93 ±3.56 days (p=0.017). Tamsulosin group stone expulsion time was lower as compared to observation group. Overall the number of doses of analgesic (diclofenac) required in tamsulosin group, it was 3.78 ± 2.82 whereas in observation group was observed to be 5.93± 1.76. The variation between number of doses of analgesic required by patients in both groups was found to statistically significant (p=0.001). Conclusions: The effectiveness of tamsulosin as a medical expulsive therapy in patients with lower ureteric calculi was higher as compared to observation group. Tamsulosin has been found to increase stone expulsion rates, reduces mean days to stone expulsion and decreases number of doses of analgesic requirement. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.155-159